The Influence of Internal Control and Client Importance on Audit Quality with Time Budget Pressure as a Moderating Variable - Yeni, Yeni (Jurnal Ilmiah Akuntansi Kesatuan, 2024)
This study aims to empirically examine the influence of internal control and client importance on audit quality, with time budget pressure as a moderating variable. The data used in this study was sourced from a questionnaire survey distributed to respondents in March via Google Forms. Respondents were selected using purposive sampling, with criteria including junior auditors, senior auditors, and Managing Partners (leaders) from audit firms (KAP) in Bogor, Jakarta, Bali, and East Java. The final sample used in this study was 50 observations. The results of this study show that client importance has a negative effect on audit quality. Internal control has a positive effect on audit quality. Time budget pressure moderates the relationship between client importance and audit quality in a positive direction. Time budget pressure moderates the relationship between internal control and audit quality in a negative direction. Time budget pressure itself has a positive effect on audit quality. Keywords: Internal Control, Client Importance, Kualitas Audit dan Time Budget Pressure